Table of Content - - (Journal of medical and pharmaceutical sciences, 2025)
Table of Content: 1. The extent of Yemeni society’s acceptance of the application of artificial intelligence in the field of dentistry A case study in the city of Taiz Dr. Ahmed Mohammed Mahmood Abdulhameed ,Eng. Amer Abdo Mohammed Sufyan 2. The Effect of Thermal Treatment on the Concentration of Common Antibiotics in Cow Milk Samples in Sudan Dr. Tafaul Awad Mohamed Alawad, Dr. Amira A.A. Behairy, Dr. Muhanad M. A. Elhag, Dr. Shakir Saleem